Inhibitory leukocyte immunoglobulin-like receptors: Immune checkpoint proteins and tumor sustaining factors. Issue 1 (2nd January 2016) - Kang, Xunlei; Kim, Jaehyup; Deng, Mi; John, Samuel; Chen, Heyu; Wu, Guojin; Phan, Hiep; Zhang, Cheng Cheng
ABSTRACT: Inhibitory leukocyte immunoglobulin-like receptors (LILRBs 1-5) transduce signals via intracellular immunoreceptor tyrosine-based inhibitory motifs (ITIMs) that recruit protein tyrosine phosphatase non-receptor type 6 (PTPN6 or SHP-1), protein tyrosine phosphatase non-receptor type 11 (PTPN11 or SHP-2), or Src homology 2 domain-containing inositol phosphatase (SHIP), leading to negative regulation of immune cell activation. Certain of these receptors also play regulatory roles in neuronal activity and osteoclast development. The activation of LILRBs on immune cells by their ligands may contribute to immune evasion by tumors. Recent studies found that several members of LILRB family are expressed by tumor cells, notably hematopoietic cancer cells, and may directly regulate cancer development and relapse as well as the activity of cancer stem cells. LILRBs thus have dual concordant roles in tumor biology – as immune checkpoint molecules and as tumor-sustaining factors. Importantly, the study of knockout mice indicated that LILRBs do not affect hematopoiesis and normal development. Therefore LILRBs may represent ideal targets for tumor treatment. This review aims to summarize current knowledge on expression patterns, ligands, signaling, and functions of LILRB family members in the context of cancer development.